Kinerja Keuangan Terungkap: Metode Du Pont dan Tobin's - Dede Hertina; Wien Dyahrini; Asep Sudrajat (Jurnal Riset Akuntansi & Perpajakan (JRAP), 2023)
The aim of this research is to analyze the financial performance using the Du Pont method as a mediator to understand the influence of DER, dividend yield, and firm size on the financial indicator Tobin's Q. The research method used is descriptive-verification. The population of this study consists of 20 companies listed in the Index High Dividend during the period 2018 to 2020. Using the saturated sample method, 20 companies from the Index High Dividend were selected as the research sample. Data analysis was conducted using the descriptive and verification approach with the structural equation modeling (SEM-PLS) technique. The research findings indicate that DER and firm size do not have a significant influence on Tobin's Q, while dividend yield and ROE Du Pont have a positive influence on Tobin's Q. Furthermore, DER and firm size have a positive influence on ROE Du Pont, but there is no significant influence of dividend yield on ROE Du Pont. ROE Du Pont functions as a mediator between DER and firm size with Tobin's Q, but it does not mediate the influence of dividend yield on ROE Du Pont. Overall, DER, dividend yield, and firm size jointly have an influence on ROE Du Pont, and ROE Du Pont also affects Tobin's Q.